The Role of Walkability, Socio-Economic and Parental Cognitive Characteristics in Long Walking Journeys to School. Issue 1 (January 2023) - Fallah Zavareh, Mohsen; Barati, Mehdi; Mamdoohi, AmirReza; Abraham, Michael
Previous research has identified the socio-economic, built environment, and psychological barriers to children walking to school. Long journeys, however, have been identified as a crucial constraint reducing the likelihood of walking to school. Determining a threshold to distinguish between long and short journeys, the present study sought to examine whether the contribution of the factors reducing walking to school differs between short and long journeys. Questionnaires were distributed among 7 to 12-year-old children in a neighborhood of Tehran ( n = 272) to be completed by parents. In addition, instead of walkability at the neighborhood level that considers walkability within a radial buffer from home or destination, we measured walkability along the school routes. ROC (Receiver Operating Characteristic) curve analysis found a threshold of 12.5 min to differentiate between long and short journeys. Walking journeys longer or shorter than the threshold were classified to be long or short, respectively. We developed two separate models, one to estimate walking for all (including long and short) journeys; and the other for only long journeys. Compared with all journeys, long walking journeys were explained by more built-environment variables. Parental attitudes toward walking were also significant in long walking journeys. However, analysis of interaction effects between walking time to school and the study variables confirmed that among all variables examined, the contribution of only environmental factors of crosswalks, walkways, and physically permeable frontages was significantly different between long and short walking journeys. Policy implications of the findings have been discussed.